Rumah Tinggal Tan Tjwan Bie di Surabaya: Studi Langgam Arsitekturnya - Santoso, Joko Triwinarto (RUAS, 2019)
In the social stratification created by the Dutch colonial government, Chinese community in the Netherlands Indies occupied the second place, after Europeans. They live scattered in various cities, one of them is Surabaya. In this city they also settled in the second place after the indigenes in terms of numbers. Tan Tjwan Bie, one of them, was known as the founder of Kebon Agung sugar factory in Malang. With the financial ability, he was able to hire Cosman Citroen, one of the leading architects in the Netherlands Indies, and Gerard Pieter Adolfs, an internationally reputed painter, to design his mansion, as well as a prominent contractor of Nedam appointed to build it until its completion in 1928. At that time, modern architecture was growing rapidly. As a collaborative work of various prominent parties with different backgrounds, this building is worthy of being examined in its architectural style. This paper aims to identify the extent of the influence of modern architecture on this mansion. This study used a combination method of historical, qualitative descriptive, and graphics methods. The result shows that various styles of modern architecture which were popular at the time could be found in the design of his mansion.